Legal pathways for China’s blue carbon conservation: a perspective of synergizing ocean and climate rule of law - Li, Haitang; Liu, Yu (Frontiers in Marine Science, 2024)
Blue carbon serves as a significant natural carbon sink and presents substantial opportunities for greenhouse gas mitigation actions. This study first elucidates the importance of blue carbon conservation and its basis in international law, and then analyzes the progress and shortcomings of China’s efforts in blue carbon protection in the areas of legislation, enforcement, and judicial practices related to ocean governance and climate change mitigation. Finally, from the perspective of coordinating ocean and climate governance, this paper proposes legal pathways to improve blue carbon conservation. In terms of legislation, it advocates for the explicit inclusion of the legal concept of “blue carbon” in the legal frameworks governing ocean and climate governance, and for the clarification of the legal status of “blue carbon credits”. In terms of regulatory enforcement, it recommends developing a detailed implementation plan to integrate blue carbon into the China Certified Emission Reduction (CCER) system, designating a regulatory body for blue carbon trading, and establishing a multi-stakeholder governance mechanism involving government, market, and society. In the judicial realm, the paper suggests issuing judicial interpretations to clarify the scope, prerequisites, and implementation of “purchasing blue carbon credit” to prevent such purchases from becoming a “free pass” that could damage marine ecosystems